Leading MSM out of the Underground: Using Transformative Leadership in Human Rights Advocacy in Malawi. - Johnson, Darrin; Rowan, Diana (Social Development Issues (Follmer Group), 2016)
In parts of Africa same-sex sexuality is punishable by imprisonment. Decriminalization of these behaviors is a growing human rights issue with important implications for HIV prevention and care for MSM. A nongovernmental organization in Malawi uses the transformative leadership model to effectively challenge existing discriminatory policies, practices, and attitudes.